Enhancing the Effectiveness of Character Education Through Teacher Personality and School Culture - Waode Emilya Megawati; Eka Suhardi; Eri Sarimanah (Universitas Pancasakti Tegal, 2026)
Character education aimed to nurture students’ moral integrity, ethical awareness, and social responsibility; however, its implementation in schools often fell short of these ideals, indicating the need to strengthen teacher-related and organizational factors. This study investigated how teacher personality enhanced the effectiveness of character education and how school culture mediated this relationship. A quantitative survey design was employed involving 197 teachers selected from 816 public junior secondary school teachers in Bogor City, Indonesia, using multistage proportional random sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicated that teacher personality positively influenced school culture and the effectiveness of character education, with school culture partially mediating this relationship.